Characterization of oral yeasts isolated from healthy individuals attended in different Colombian dental clinics (2019)
The aim of this study was to identify the most frequent yeasts in the oral cavity of adult individuals without immune disorders and to associate the presence of these oral yeasts with different characteristics of each individual. Oral rinse samples were obtained from 96 healthy adults and cultured in Sabouraud dextrose agar media and CHROMagar. Yeasts were identified by sequencing the D1/D2 region of the 28S rRNA gene. Probable association among the socio-demographic characteristics, body mass index, family and personal medical history, oral hygiene, tobacco and/or alcohol consumption habits and presence of oral fungi was analyzed. Contingency tables and logistic regression were employed to evaluate possible relationships between the presence of oral fungi and mixed colonization with these variables. 57.3% of the healthy individuals had oral yeasts and 21.8% had mixed colonization. The most prevalent yeasts were Candida albicans (52%), C. parapsilosis (17.9%), and C. dubliniensis (7.57%). Yeasts with most frequently mixed colonization were C. albicans and C. parapsilosis. No relationships were found among the variables analyzed. However, the presence of mixed colonization was related to the presence of dental prostheses (P less than 0.006), dental apparatuses (P=0.016) and O'Leary index (P=0.012). This is the first study that characterized oral yeasts in Colombian healthy individuals, determined the most prevalent oral yeasts C. albicans, C. parapsilosis and C. dublinensis and an association of mixed colonization with the use of dental prostheses and aparatology and poor hygiene. © 2019 by the Journal of Biomedical Research.